For love of animals : Christian ethics, consistent action - Camosy, Charles Christopher (Cincinnati, OH : Franciscan Media, 2013)
"For Love of Animals is an honest and thoughtful look at our responsibility as Christians with respect to animals. Many Christians misunderstand both history and their own tradition in thinking about animals. They are joined by prominent secular thinkers who blame Christianity for the Western world's failure to seriously consider the moral status of animals. This book explains how traditional Christian ideas and principles--like nonviolence, concern for the vulnerable, respect for life, stewardship of God's creation, and rejection of consumerism--require us to treat animals morally"--
Chapters are followed by questions for discussion.
Includes bibliographical references.
Description based on print version record.
Keywords: Animals -- Religious aspects -- Christianity; Animal welfare -- Religious aspects -- Christianity; Christian ethics; RELIGION / Ethics; RELIGION / Christian Theology / Ethics; RELIGION / Christianity / Catholic; Animal welfare -- Religious aspects -- Christianity; Animals -- Religious aspects -- Christianity; Christian ethics; Electronic books